Level of Oral Reading Fluency of Learners: Basis for An Intervention Plan - Binaloga, Jeneve (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aimed to determine the level of oral reading fluency of Grade 4 learners in Culban Elementary School, District 10 in the Division of Himamaylan City during the 3rd grading period of SY 2019-2020. The variables included were sex, parents’ highest educational attainment and size of the family. The study covered the following areas: Speed, Accuracy and Prosody. The result of the study showed that the oral reading fluency of learners’ according showed the following results: Speed – Frustration level, Accuracy – Independent and for Prosody, Approaching Fluency. The oral reading fluency of learners’ when grouped according to aforementioned variables showed these results: Speed – Frustration level, Accuracy – Independent and for Prosody, Approaching Fluency. There was a significant difference in the oral reading fluency of learners when grouped and compared according to sex; there was no-significant difference when grouped according to parent’s highest educational attainment and size of the family.